PROFILE OF CRITICAL AND CREATIVE THINKING SKILLS OF STUDENTS OF BIOLOGY EDUCATION STUDY PROGRAM OF UIN ALAUDDIN MAKASSAR: NEEDS ANALYSIS DEVELOPMENT OF STILLALI MODEL - Ali, Ahmad; Palennari, Muhiddin; Abd. Muis; Jabbar, Asniati (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2023)
Abstract: This study aims to analyze the development needs of the STILLaLI Model. This study discusses the students’ profile of critical thinking skills and creative thinking skills in the Biology Study Program at UIN Alauddin Makassar. This study used quantitative descriptive research with 46 students as respondents. Critical thinking skills data was collected using a test technique, and creative thinking skills data was collected through surveys. The results showed that critical thinking skills were in the less critical category with an average score of 53.09, while creative thinking skills were in the creative enough category with an average score of 58.02. It is necessary to develop a learning model that is able to improve the critical and creative thinking skills of students of the Biology Education study program at UIN Alauddin Makassar, namely the STILLaLI Model. Abstrak: Penelitian ini bertujuan untuk menganalisis kebutuhan pengembangan Model STILLaLI. Penelitian ini membahas profil ketrampilan berpikir kritis dan keterampilan berpikir kreatif mahasiswa Program Studi pendidikan Biologi UIN Alauddin Makassar. Penelitian ini merupakan penelitian deskriptif kuantitatif dengan 46 mahasiswa sebagai responden. Data keterampuilan berpikir kritis dikumpulkan dengan teknik tes. Data keterampilan berpikir kreatif dikumpulkan melalui survey. Hasil penelitian menunjukkan keterampilan berpikir kritis pada kategori kurang kritis dengan nilai rata-rata 53,09, sedangkan keterampilan berpikir kreatif berada pada kategori cukup kreatif dengan nilai rata-rata 58,02. Perlu dilakukan pengembangan model pembelajaran yang mampu meningkatkan keterampilan berpikir kritis dan kreatif mahasiswa program studi Pendidikan Biologi UIN Alauddin Makassar yakni Model STILLaLI.